THU0327 Real world (RW) experience with an anti-il-17a inhibitor in biologic naÏve and biologic experienced psoriatic arthritis (PSA) patients. (12th June 2018) - Moon, R.; Hill, J.; Booth, N.; Lobosco, S.
Abstract : Background: Two IL-17A inhibitors are approved for the treatment of PsA, ixekizumab and secukinumab. At the time of this survey, real world evidence was only available for secukinumab, which was approved for PsA in 2016 in EU, Australia and Switzerland. Secukinumab label dose for PsA patients with either concomitant moderate to severe plaque psoriasis or anti-TNFα inadequate responders is 300 mg. For other patients, the recommended dose is 150 mg. All patients receive a loading dose regimen by S.C. injection at Weeks 0, 1, 2, 3 and 4, followed by monthly maintenance dose. Little data are published on the RW utilisation of secukinumab in PsA. Objectives: Describe RW dose utilisation of an anti-IL-17A inhibitor, among biologic naïve and biologic experienced PsA patients. Methods: Data from a chart review study conducted in 2017 across France, Germany, Italy, Spain, UK, Australia and Switzerland where secukinumab is reimbursed were used. Specialists were recruited by field-based interviewers, and provided information on demographics, Body Surface Area (BSA), time since diagnosis and treatment for their adult PsA patients currently receiving secukinumab. Results: 212 rheumatologists, 89 dermatologists, 1 orthopedist provided data for 1451 patients. Mean age 50.6 years, 47% female, mean time since PsA diagnosis 5.9 years and 86% had concomitant psoriasis. 96% received prior csDMARD(s) and 8% prior apremilast. 29% (425) were biologic naïve and 71% (1024) biologic experienced (limited differences between specialists: 74% rheumatologists; 63% dermatologists). 34%, 24%, and 13% received, 1, 2, and 3+prior biologics respectively. Among biologic naïve patients on 150 mg, 36% (52/145) had a BSA ≥10%, where the recommended dose is 300 mg at secukinumab initiation. 29% (274/930) of biologic experienced patients received secukinumab at 150 mg, not the recommended 300 mg dose (figure 1) Conclusions: In the RW, secukinumab is prescribed mainly in biologic experienced patients (71%) and is not universally prescribed at the recommended dose for PsA. Specifically, of those who are biologic naïve (29%), 36% of patients on 150 mg had moderate to severe psoriasis, which is outside the recommended dose. Further RW experience is needed for ixekizumab. Acknowledgements: Acknowledgements: This chart review study was designed and run by Adelphi Real World. The study was supported by a number of pharmaceutical companies, including Eli Lilly and Company. This specific analysis and abstract was supported by Eli Lilly and Company. Disclosure of Interest: R. Moon: None declared, J. Hill Grant/research support from: Eli Lilly and Company, Employee of: Eli Lilly and Company, N. Booth: None declared, S. Lobosco: None declared